Local traditional ecological knowledge about hay management practices in wetlands of the Biebrza Valley, Poland - Joanna Sucholas; Zsolt Molnár; Łukasz Łuczaj; Peter Poschlod (BMC, 2022)
Abstract Background The Biebrza Valley is one of the largest complexes of wetlands (floodplain and percolation mire) and conservation sites in Central Europe. Local communities have managed the area extensively for subsistence and farming purposes for centuries; nonetheless, since the 1960s, hand mowing and livestock grazing have been gradually ceasing due to the intensification of farming, and wetlands have undergone natural succession. Currently, the protection of this vast ecosystem is challenging. Despite its remarkable cultural origin, the complexity of the traditional practices and knowledge of local people have never been studied comprehensively. Therefore, we found it urgent to explore if traditional ecological knowledge that could be used in conservation management of the area still exists among the local community. Methods We interviewed 42 inhabitants of seven villages located in the Lower Basin of the Biebrza Valley (NE-Poland) in the consecutive years 2018-2020. We applied semi-structured, repeated interviews with farmers (aged 29-89), each lasting several hours. By using different ethnoecological methods (visual stimuli, walks in wetlands, co-mapping of the area), we explored traditional knowledge on the plants, landscape and traditional management of wetlands. Results Farmers from the oldest generation, who used to manage wetlands with scythes, shared the deepest ecological knowledge. Local people divided wetlands into zones differentiated by vegetation type and hay quality. Depending on plant composition, people managed wetlands under a mixed regime: mowing once or twice a year during periods that ensured good hay quality and pasturing various livestock: cattle, horses, sheep, pigs and fowl. We identified at least 50 plant ethnospecies, which were described exhaustively by their habitat, morphological features, and mowing and grazing value. Conclusions The local community in the Biebrza Valley shared a deep traditional ecological knowledge and had a good memory of traditional farming practices. Research confirmed the unquestionable cultural origin of the local ecosystem, therefore in conservation endeavours the area should be treated first and foremost as a cultural landscape. The documented exceptional local perception of the wetland landscape, elements of traditional knowledge and complex farming practices should be considered for inclusion into conservation management, and cooperation with the local community should also be taken into account.